Isolated Osteochondral Autograft Versus Allograft Transplantation for the Treatment of Symptomatic Cartilage Lesions of the Knee: A Systematic Review and Meta-analysis. Issue 3 (March 2023) - Trofa, David P.; Hong, Ian S.; Lopez, Cesar D.; Rao, Allison J.; Yu, Ziqing; Odum, Susan M.; Moorman, Claude T.; Piasecki, Dana P.; Fleischli, James E.; Saltzman, Bryan M.
Background: Focal cartilage lesions of the knee remain a difficult entity to treat. Current treatment options include arthroscopic debridement, microfracture, autograft or allograft osteochondral transplantation, and cell-based therapies such as autologous chondrocyte transplantation. Osteochondral transplantation techniques restore the normal topography of the condyles and provide mature hyaline cartilage in a single-stage procedure. However, clinical outcomes comparing autograft versus allograft techniques are scarce. Purpose: To perform a comprehensive systematic review and meta-analysis of high-quality studies to evaluate the results of osteochondral autograft and allograft transplantation for the treatment of symptomatic cartilage defects of the knee. Study Design: Systematic review and meta-analysis; Level of evidence, 2. Methods: A comprehensive search of the literature was conducted using various databases. Inclusion criteria were level 1 or 2 original studies, studies with patients reporting knee cartilage injuries and chondral defects, mean follow-up ≥2 years, and studies focusing on osteochondral transplant techniques. Exclusion criteria were studies with nonknee chondral defects, studies reporting clinical outcomes of osteochondral autograft or allograft combined with other procedures, animal studies, cadaveric studies, non–English language studies, case reports, and reviews or editorials. Primary outcomes included patient-reported outcomes and failure rates associated with both techniques, and factors such as lesion size, age, sex, and the number of plugs transplanted were assessed. Metaregression using a mixed-effects model was utilized for meta-analyses. Results: The search resulted in 20 included studies with 364 cases of osteochondral autograft and 272 cases of osteochondral allograft. Mean postoperative survival was 88.2% in the osteochondral autograft cohort as compared with 87.2% in the osteochondral allograft cohort at 5.4 and 5.2 years, respectively ( P = .6605). Patient-reported outcomes improved by an average of 65.1% and 81.1% after osteochondral autograft and allograft, respectively ( P = .0001). However, meta-analysis revealed no significant difference in patient-reported outcome percentage change between osteochondral autograft and allograft ( P = .97) and a coefficient of 0.033 (95% CI, –1.91 to 1.98). Meta-analysis of the relative risk of graft failure after osteochondral autograft versus allograft showed no significant differences ( P = .66) and a coefficient of 0.114 (95% CI, –0.46 to 0.69). Furthermore, the regression did not find other predictors (mean age, percentage of female patients, lesion size, number of plugs/grafts used, and treatment location) that may have significantly affected patient-reported outcome percentage change or postoperative failure between osteochondral autograft versus allograft. Conclusion: Osteochondral autograft and allograft result in favorable patient-reported outcomes and graft survival rates at medium-term follow-up. While predictors for outcomes such as mean age, percentage of female patients, lesion size, number of plugs/grafts used, and treatment location did not affect the comparison of the 2 cohorts, proper patient selection for either procedure remains paramount to the success and potentially long-term viability of the graft.